Legal Markets - Hadfield, Gillian K. (Journal of Economic Literature, 2022)
The existence of an effective legal system is assumed throughout economic analysis, and yet there has been little study of the economics of legal markets themselves. Research to date has focused narrowly on the economics of markets for lawyers. In this review, I distinguish legal markets from the market for lawyers and show how excessive regulation of our legal markets—by lawyers themselves—distorts economic activity and growth. It does so primarily by inhibiting investment in the legal and regulatory technologies needed to respond to the transformation of the economy wrought by globalization, digitization, aspirations for inclusion, and the coming of artificial intelligence. (JEL J44, K00, K40, L84)